Awareness of contemporary lexical change for professional competence in English language education. - Mohideen, Haja; Mohideen, Shamimah (EUROJOURNALS, 2010)

(untitled)
Influential languages such as English reinvent themselves and prosper. The ongoing developments taking place in such dynamic languages make it imperative for language users to be up-to-date and be familiar with the changes affecting the language they are professionally involved with, more so those involved with its instruction. Languge change, especially lexical change, may be observed from various sources.